Colonization of lettuce rhizosphere and roots by tagged Streptomyces - Bonaldi, Maria; Chen, Xiaoyulong; Kunova, Andrea; Pizzatti, Cristina; Saracchi, Marco; Cortesi, Paolo (Frontiers in Microbiology, 2015)
Beneficial microorganisms are increasingly used in agriculture, but their efficacy often fails due to limited knowledge of their interactions with plants and other microorganisms present in rhizosphere. We studied spatio-temporal colonization dynamics of lettuce roots and rhizosphere by genetically modified Streptomyces spp. Five Streptomyces strains, strongly inhibiting in vitro the major soil-borne pathogen of horticultural crops, Sclerotinia sclerotiorum, were transformed with pIJ8641 plasmid harboring an enhanced green fluorescent protein marker and resistance to apramycin. The fitness of transformants was compared to the wild-type strains and all of them grew and sporulated at similar rates and retained the production of enzymes and selected secondary metabolites as well as in vitro inhibition of S. sclerotiorum. The tagged ZEA17I strain was selected to study the dynamics of lettuce roots and rhizosphere colonization in non-sterile growth substrate. The transformed strain was able to colonize soil, developing roots and rhizosphere. When the strain was inoculated directly on the growth substrate, significantly more t-ZEA17I was re-isolated both from the rhizosphere and the roots when compared to the amount obtained after seed coating. The re-isolation from the rhizosphere and the inner tissues of surface-sterilized lettuce roots demonstrated that t-ZEA17I is both rhizospheric and endophytic.